Balinese Indigenous Knowledge about Water : A Way to Achieve Water Sustainability - Saraswaty, Amrita Nugraheni; Kesuma, Wayan Gita; Yasa, Murjana (Jurnal Ekonomi Kuantitatif Terapan, 2021)
For the Balinese, water is essential for their ritual-based culture. Water is an entity to complete Balinese everyday life, especially the spiritual aspects that need holy water for rituals. This study aims to analyze the influence of Balinese indigenous knowledge about groundwater management, membership of the indigenous organizations, perception of the catchment areas, and water resources alternatives to groundwater resource conservation amongst Balinese. To address this, a survey of a representative sample of 139 Balinese adults in SARBAGITA (Denpasar Regency, Badung Regency, Gianyar Regency, and Tabanan Regency) has been conducted. With logistic regression model, this study found that knowledge and method used in respondents' households when water is limited are the most significant factor that affects respondents' willingness to participate in sacred springs conservation program.